A Review of the Use of Aaker’s Methodology within the Brand Personality Construct: A Review of Extant Literature - Oladipupo Folorunsho Ajeyalemi; Bolajoko Nkemdilim Dixon-Ogbechie (TIJAB (The International Journal of Applied Business), 2020)
Anthropomorphism is the belief that brands can possess human characteristics, which raises a tendency to assign human traits to inanimate objects. It is on this premise that Brand Personality takes its roots.  Several studies in the measurement and influence of Brand Personality abound leading to increasing arguments on the most appropriate methods to be used to measure Brand Personality.  However, Aaker’s methodology stands out prominently in the Brand Personality domain.  This study attempts to review the Brand Personality literature to identify the extent that this methodology has been used.  The objectives of this study are to identify the scope and limitation of Aaker’s (1997) Brand Personality construct, identify the literature on Brand Personality and identify the use of Aaker’s (1997) methodology in scale development. Using a qualitative design, consecutive sampling was used to analyze the identified literature on Brand Personality. The resulting data was analyzed using frequency and pictorial analysis and several tables presenting the review of the literature were developed.